Occurrence of yeasts, enterococci and other enteric bacteria in subgingival biofilm of HIV-positive patients with chronic gingivitis and necrotizing periodontitis - Jardim Júnior, Elerson Gaetti [UNESP]; Nakano, Viviane; Wahasugui, Thais C.; Cabral, Fátima C.; Gamba, Rosa; Avila-Campos, Mario Julio (Sociedade Brasileira de Microbiologia, 2008)
O objetivo desse estudo foi avaliar a ocorrência de bactérias entéricas e leveduras no biofilme subgengival de pacientes HIV-positivos com gengivite crônica ou periodontite necrosante. Os pacientes foram submetidos a exame clínico e radiográfico e de higiene bucal, sangramento à sondagem, condições gengivais e a perda de inserção. Os espécimes clínicos de sulcos gengivais ou bolsas periodontais foram inoculados em ágar Sabouraud dextrose com 100 mg/ml de cloranfenicol, água peptonada, caldo EVA, ágar EMB, ágar SS, ágar Bile esculina e ágar verde brilhante. O cultivo de leveduras foi realizado à temperatura ambiente, de 3-7 dias; das enterobactérias a 37ºC de 24-48 h. A identificação das leveduras foi realizada pela assimilação de carbono e nitrogênio, fermentação de açucares e formação de tubo germinativo. As bactérias de acordo com a morfologia celular e colonial e testes bioquímicos. Foram identificadas Candida albicans e sua prevalência foi maior em pacientes com contagens de CD4+ < 200/mm³, e sua ocorrência foi afetada pela extensão da destruição periodontal (P = 0,0345). Enterobacteriaceae e enterococos foram detectados em 32,5% dos pacientes com periodontite necrosante. As enterobactérias foram Enterobacter sakazakii, E. cloacae, Serratia liquefaciens, Klebsiella oxytoca e Enterococcus sp. Concluiu-se que bactérias patogênicas exógenas à cavidade bucal e C. albicans podem ser detectadas no biofilme subgengival de pacientes HIV-positivos com periodontite necrosante e gengivite.

The purpose of this study was to determine the prevalence of enteric bacteria and yeasts in biofilm of 80 HIV-positive patients with plaque-associated gingivitis or necrotizing periodontitis. Patients were subjected to extra, intra oral and radiographic examinations. The oral hygiene, bleeding on probing, gingival conditions, and attachment loss were evaluated. Clinical specimens were collected from gingival crevices or periodontal pockets, transferred to VMGA III, diluted and transferred to Sabouraud Dextrose agar with 100 µg/ml of chloramphenicol, peptone water, EVA broth, EMB agar, SS agar, Bile esculin agar and Brilliant green agar. Isolation of yeasts was carried out at room temperature, for 3-7 days; and for the isolation of enteric microorganisms plates were incubated at 37ºC, for 24-48 h. The yeasts identification was performed according to the carbon and nitrogen assimilation, fermentation of carbohydrates and germ tube formation. Bacteria were identified according to their colonial and cellular morphologies and biochemical tests. Yeasts were identified as Candida albicans and its occurrence was more common in patients with CD4+ below 200/mm³ and was affected by the extension of periodontal involvement (P = 0.0345). Enteric bacteria recovered from clinical specimens were identified as Enterobacter sakazakii, Enterobacter cloacae, Serratia liquefaciens, Klebsiella oxytoca and Enterococcus sp. Enterobacteriaceae and enterococci were detected in 32.5% of clinical samples from patients with necrotizing periodontitis. In conclusion, non-oral pathogenic bacteria and C. albicans were more prevalent in periodontal sites of HIV-positive patients with necrotizing periodontitis and chronic gingivitis.
Ocorrência de leveduras, enterococos e outras bactérias entéricas no biofilme subgengival de pacientes HIV-positivos com gengivite crônica e periodontite necrosante
Keywords: HIV; gengivite; periodontite necrozante; Candida albicans; enterococos; enterobacterias; HIV patients; Candida albicans; enterococci; enterobacteria